Topeng Sebagai Ide Penciptaan Karya Seni Lukis Ekspresionis - Yogi Hendika Pratama (Lembaga Pengembangan Kinerja Dosen, 2024)
The aim of this work is to represent the author's personal concerns which he wishes to express in his final assignment of creating a work of painting, based on personal experiences in the process of making friends over the years. Every human being has their own process in making friends, during which time hypocrisy will occur in friendship. There are several stages carried out according to the method used in creating the work, namely: 1). Preparation is the initial stage in creating a work of art starting from looking for ideas and concepts. 2). Elaboration is a main idea that has been determined and will later be expressed in a work of Expressionist Painting. 3). Synthesis is the steps in creating a work. 4). Concept Realization is a process stage in work and 5). Completion is the final stage in the work. A total of ten paintings measuring 120 cm x 100 cm and 100 cm x 100 cm with acrylic media on canvas. Each work displays a different facial anatomical figure. namely